The Effect Of the Implementation of Plant Lay Out the Rightand Availability of Raw Materials on the Production Flow In Indo Karuna Steel - Edi Suprapto; Denok Sunarsi (International Journal of Education, Information Technology, and Others, 2020)
This study aims to determine the effect of Plant Layout and the availability of raw materials on the smooth production at PT. Indo Karuna Steel. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Plant Layout has a significant effect on the smoothness of production by 46.4%, the hypothesis test obtained t count> t table or (7.390> 1.998). The availability of raw materials has a significant effect on the smooth production of 45.9%, the hypothesis test is obtained t count> t table or (7.304> 1.998). Plant Layout and the availability of raw materials simultaneously have a significant effect on the smoothness of production by 57.1%, the hypothesis test obtained F count> F table or (41.268> 2.750).